Hubungan Mikrobiota Saluran Cerna dengan Kadar Hb dan Status Gizi Anak Di Puskesmas Kaliwates - Yuningsih, Yuningsih; Zannah, Ai Nur; Sari, Asri Iman; Handayani, Ririn (ARTERI : Jurnal Ilmu Kesehatan, 2024)
The issue of nutritional status, particularly stunting in children, is a global concern that requires serious attention. This research aims to investigate the relationship between gut microbiota and hemoglobin (HB) levels and nutritional status in children at the Kaliwates Health Center. This type of research includes observational analytics with a cross-sectional study design. Sampling was done by purposive sampling, resulting in 19 respondents who met the inclusion criteria. The analysis of this study includes univariate and bivariate analysis with statistical tests using Chi Square. The research instruments used were digital Hb tests and laboratory feces examinations. The results of the univariate analysis using the Chi Square test showed that the majority of children's gut microbiota was abnormal (89.5%), while the majority of HB levels were normal (42.1%) and the majority of nutritional status was in the short category (47.4%). The bivariate analysis results of the relationship between microbiota and Hb levels showed a p-value of 0.215 (p-value>0.05), while the bivariate analysis results of the relationship between microbiota and nutritional status showed a p-value of 0.000 (p-value<0.05). The conclusion of this study is that there is no relationship between gut microbiota and Hb levels, but there is a significant relationship between gut microbiota and nutritional status.children's nutritional status, including the role of the microbiota in digestion and absorption of nutrients.